Samlingsformidling gennem tematiske værkfortegnelser - Geertinger, Axel Teich (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2019)
Axel Teich Geertinger: Contextualising Library Collections through Thematic Catalogues Between the years 2014 and 2019, Dansk Center for Musikudgivelse (DCM) (Danish centre for Music Editing) has published thematic-bibliographic catalogues of the works of four composers, in both digital and printed editions: Carl Nielsen, Johann Adolph Scheibe, J.P.E. Hartmann and Niels W. Gade. The concept and the software behind it were developed by DCM concurrently with the work on the actual catalogues’. DCM’s catalogues of the works are in keeping with a long tradition within musicology, in which such catalogues are a standard tool. In view of the particular situation for sources in Denmark, on the one hand, where most of the relevant material concerning Danish composers can be found in the Royal Danish Library’s collections, and the conversion of the catalogue concept to digital media on the other, DCM’s catalogues of works also gain a different perspective, so that they are not just a reference work for researchers, students and musicians, but also actual dissemination of the collection. While library catalogues’ perspective is fundamentally concentrated on specific items, catalogues of works – as the name says – concentrate on works. The works perspective is appropriate to provide an overview of all the material and information associated with a work and can thus put each source into a context. With links directly to library entries and digitisations, the catalogue can offer an alternative, more generalised and holistic approach to the library’s material than library catalogues. There are also links to related material, such as concurrent reviews in Mediestream. This article presents the catalogue of works concept and discusses its prospects and limitations, in particular from a library perspective.